LINGVOMADANIY INTERFERENSIYA VA UNING TIL ORGANISHDAGI SALBIY TA SIRI RUS VA OZBEK TILLARI VA MADANIYATI MISOLIDA - Istoda Rasulova (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article describes the errors of linguocultural interference that arise in the process of learning a foreign language, their reasons, the close connection of language with culture, a comparison of Russian and Uzbek cultures, ways to overcome interference speech errors.